Pure Total Flavonoids From Citrus Protect Against Nonsteroidal Anti-inflammatory Drug-Induced Small Intestine Injury by Promoting Autophagy in vivo and in vitro - Chen, Shanshan; Jiang, Jianping; Chao, Guanqun; Hong, Xiaojie; Cao, Haijun; Zhang, Shuo (Frontiers in Pharmacology, 2021)
Small intestine injury is an adverse effect of non-steroidal anti-inflammatory drugs (NSAIDs) that urgently needs to be addressed for their safe application. Although pure total flavonoids from citrus (PTFC) has been marketed for the treatment of digestive diseases, its effects on small intestine injury and the underlying mechanism of action remain unknown. This study aimed to investigate the potential role of autophagy in the mechanism of diclofenac-induced intestinal injury in vivo and in vitro and to demonstrate the protective effects of PTFC against NSAID-induced small intestine disease. The results of qRT-PCR, western blotting, and immunohistochemistry showed that the expression levels of autophagy-related 5 (Atg5), light chain 3 (LC3)-II, and tight junction (TJ) proteins ZO-1, claudin-1, and occludin were decreased in NSAID-induced small intestine injury rats and IEC-6 cells compared with the control groups. In the PTFC group, Atg5 and LC3-II expression, TJ protein expression, and the LC3-II/LC3-I ratio increased. Furthermore, the mechanism by which PTFC promotes autophagy in vivo and in vitro was evaluated by western blotting. Expression levels of p-PI3K and p-Akt both increased in the intestine disease-induced rat model group compared with the control, but decreased in the PTFC group. Autophagy of IEC-6 cells was upregulated after treatment with a PI3K inhibitor, and the upregulation was significantly more after PTFC treatment, suggesting PTFC promoted autophagy through the PI3K/Akt signaling pathway. In conclusion, PTFC protected intestinal barrier integrity by promoting autophagy, which demonstrated potential as a therapeutic candidate for NSAID-induced small intestine injury.